2013
DOI: 10.1182/blood-2012-12-470765
|View full text |Cite
|
Sign up to set email alerts
|

LIM kinase-1 selectively promotes glycoprotein Ib-IX–mediated TXA2 synthesis, platelet activation, and thrombosis

Abstract: Key Points Role for LIMK1 in GPIb-IX–dependent cPLA2 activation, TXA2 synthesis, and platelet activation independent of its role in actin polymerization. LIMK1 is important in arterial thrombosis in vivo but appears to be dispensable for hemostasis, suggesting a new antithrombotic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 41 publications
(64 reference statements)
1
24
0
Order By: Relevance
“…We next evaluated proplatelet formation on a fibrinogen matrix. For WT MKs, the percentage of proplatelet-forming MKs was similar in LIMKi-and vehicle-treated (DMSO) cells ( Figure 6C), which is compatible with the normal platelet count reported in LIMK-deficient mice (26). Interestingly, while the percentage of 2B MKs that formed proplatelets remained low in the presence of vehicle (18% ± 1%), treatment of 2B MKs with LIMKi restored proplatelet formation to a level similar to that of vehicle-treated WT MKs (43% ± 2% and 52% ± 10% in LIMKi-treated 2B MKs and vehicle-treated WT MKs, respectively; P > 0.05; Figure 6C).…”
Section: B and D-g)supporting
confidence: 87%
See 1 more Smart Citation
“…We next evaluated proplatelet formation on a fibrinogen matrix. For WT MKs, the percentage of proplatelet-forming MKs was similar in LIMKi-and vehicle-treated (DMSO) cells ( Figure 6C), which is compatible with the normal platelet count reported in LIMK-deficient mice (26). Interestingly, while the percentage of 2B MKs that formed proplatelets remained low in the presence of vehicle (18% ± 1%), treatment of 2B MKs with LIMKi restored proplatelet formation to a level similar to that of vehicle-treated WT MKs (43% ± 2% and 52% ± 10% in LIMKi-treated 2B MKs and vehicle-treated WT MKs, respectively; P > 0.05; Figure 6C).…”
Section: B and D-g)supporting
confidence: 87%
“…Two aspects are of relevance in this regard. First, it has been reported that artificial, ristocetin-stimulated complex formation between vWF and GPIbα induces activation of the LIMK/cofilin pathway (26). We therefore considered the possibility that outside-in signaling induced upon complex formation by freshly secreted vWF/p.V1316M and cell-surface-exposed GPIbα could be responsible for the activation of the LIMK/ cofilin pathway.…”
Section: V1316m (2b) Megakaryocytes (Mks)mentioning
confidence: 99%
“…Accordingly, PAK may regulate platelet actin dynamics through the LIMK1-mediated phosphorylation of cofilin. Intriguingly, LIMK1 also contributes to platelet function through glycoprotein Ib-IXmediated TxA2 synthesis; however, the roles of PAK phosphorylation actin-independent processes such as platelet TxA2 synthesis remain to be examined (16,36,37). Together with data demonstrating a role for PAK in thrombin-mediated platelet activation, these findings connect platelet Rho GTPase signaling to a system of PAK effectors with central roles in platelet physiological functions, including lamellipodia formation, aggregation, and calcium-mediated phosphatidylserine exposure.…”
Section: Discussionmentioning
confidence: 86%
“…In this context, we note that while LIMK1 -/- platelets showed reduced actin polymerization only late after stimulation [58], the specific inhibition of the Rho kinase that phosphorylates and activates LIMK1 results in significant F-actin level increase in unstimulated platelets [19]. This finding is reminiscent of the increased F-actin ratios in Pdlim7-deficient platelets (Fig 8).…”
Section: Discussionmentioning
confidence: 89%